Public education plays vital role in ICT development - New Sabah Times, English (KK) (New Sabah Times, 2016)
KOTA KINABALU: Public educational institutions play a vital'role to assist the government in spearheading the development of information and communication technology (ICT) to make it more accessible to, all members of society, including marginalised communities.